Genetic testing preferences and intentions in patients with clinically diagnosed familial hypercholesterolemia. Issue 6 (25th November 2019) - Wand, Hannah; Sturm, Amy C.; Erby, Lori; Kindt, Iris; Klein, William M.P.
Abstract: Purpose: Familial hypercholesterolemia (FH) is a common Mendelian disorder characterized by elevated LDL cholesterol levels, which if untreated can cause premature heart disease. Less than 10% of cases in the United States are diagnosed . This study investigates decision‐making factors associated with intentions to have FH genetic testing among patients clinically diagnosed with FH. Methods: Fifty‐three clinically diagnosed adults with FH and no genetic testing were recruited through the FH Foundation and lipid clinics. Participants completed a survey containing items capturing various reasons to engage in genetic testing. Results: Exploratory factor analysis of survey items identified three factors: (a) aversion to FH genetic information, (b) curiosity regarding medical/family history, (c) and psychological reassurance. Psychological reassurance was, in turn, the only significant predictor of genetic testing intentions. The positive effect of reassurance on genetic testing intention was moderated by aversion such that individuals who were low in reassurance were more inclined to decline testing if aversion was high. Conclusion: Findings suggest that clinically diagnosed patients' decisions about FH genetic testing are driven principally by psychological reassurance, particularly when low in aversion to FH genetic information.